Catalytic effect of industrial waste carbide slag on pyrolysis of low-rank coal. (15th February 2023) - Ban, Yanpeng; Jin, Lijun; Wang, Kechao; Li, Yang; Yang, He; Hu, Haoquan
Abstract: Calcium-catalyzed coal pyrolysis to light tar is an attractive technology in coal clean conversion. The pyrolysis behavior and product distribution of low-rank coal over carbide slag (CS) were investigated by a thermogravimetric analyzer, fixed-bed reactor, and in-situ pyrolysis vacuum ultraviolet photoionization time-of-flight mass spectrometry ( in-situ Py-VUVPI-MS). The results indicated that CS impregnation has a more significant effect on coal pyrolysis products than mechanical mixing and layered packing. The addition of CS makes coal pyrolysis tar significantly lighter, and the pitch content decreases from 33.5  wt. % without CS to 8.0  wt. % with CS impregnation but also makes benzenes and phenols content reduced by 16.4% and 55.5%, respectively. In-situ Py-VUVPI-MS analysis revealed that the decrease of benzenes content is mainly due to the secondary reaction of primary products catalyzed by calcium in CS, while the decrease of phenols content is mainly from the changed reaction path of oxygen-containing structure in coal caused by calcium catalysis. This work provides a theoretical basis for experimental research and practical application of coal pyrolysis catalyzed by CS, and the high catalytic activity, low cost, and abundant storage make the waste CS a promising Ca-based catalyst in coal pyrolysis. Graphical abstract: Image 1 Highlights: Catalytic pyrolysis of low-rank coal using carbide slag (CS) as catalyst was studied. Addition of CS performed an excellent effect on obtaining high-quality oil. CS is an efficient catalyst for pitch and phenols oil conversion. CS is expected to develop as the novel Ca-based low-cost catalyst for coal pyrolysis.